2006
DOI: 10.1016/j.sleep.2006.03.019
|View full text |Cite
|
Sign up to set email alerts
|

Stress-related sleep disturbance and polysomnographic response to caffeine

Abstract: Background and purpose-To determine the sleep response to caffeine in individuals vulnerable to stress-related sleep disturbance as measured by polysomnography.Patients and methods-Eleven healthy individuals without insomnia scoring low (4 women, mean age=32.64 ± 15.46 years) and 10 healthy individuals also without insomnia scoring high (6 women, mean age=34.20 ± 13.73 years) on a measure of vulnerability to stress-related sleep disturbance were studied in a laboratory protocol. A moderate-low dose of caffeine… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
61
0
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 89 publications
(67 citation statements)
references
References 32 publications
4
61
0
1
Order By: Relevance
“…14,15 Despite the increased use of the FIRST questionnaire to assess stressrelated sleep reactivity in men and non-pregnant women, 14,16,17 the instrument has not, to our knowledge, been used to assess BRIEF SUMMARY Current Knowledge/Study Rationale: The Ford Insomnia Response to Stress Test (FIRST) questionnaire has emerged as a broadly used instrument that assesses individual's vulnerability to situational insomnia under stressful conditions. Despite the increased use of the FIRST questionnaire to assess stress-related sleep reactivity in men and non-pregnant women, the instrument has not been used to assess stress-related sleep reactivity in pregnant women.…”
Section: Psychometric Evaluation Of the Ford Insomnia Response To Strmentioning
confidence: 99%
See 2 more Smart Citations
“…14,15 Despite the increased use of the FIRST questionnaire to assess stressrelated sleep reactivity in men and non-pregnant women, 14,16,17 the instrument has not, to our knowledge, been used to assess BRIEF SUMMARY Current Knowledge/Study Rationale: The Ford Insomnia Response to Stress Test (FIRST) questionnaire has emerged as a broadly used instrument that assesses individual's vulnerability to situational insomnia under stressful conditions. Despite the increased use of the FIRST questionnaire to assess stress-related sleep reactivity in men and non-pregnant women, the instrument has not been used to assess stress-related sleep reactivity in pregnant women.…”
Section: Psychometric Evaluation Of the Ford Insomnia Response To Strmentioning
confidence: 99%
“…21 Consistent with prior studies in the present study, we used the median score (12) to define high and low FIRST score groups. 16,[21][22][23][24] Patient Health Questionnaire-9 (PHQ-9)…”
Section: Ford Insomnia Response To Stress Test (First)mentioning
confidence: 99%
See 1 more Smart Citation
“…It was found that feeling tired in the morning induced high caffeine use which was associated with subsequent impaired sleep, indicating that cause and effect concerning the relation between caffeine and impaired sleep is not always clear. Another factor that may induce sleep disturbance in interaction with caffeine is vulnerability to stress (Drake et al, 2006). Drake and colleagues showed that individuals with an objectively identified vulnerability to stress-induced sleep disturbance showed a stronger sleep-reactivity in response to a 3-mg/kg BW caffeine challenge than nonvulnerable individuals.…”
Section: Caffeine and Recovery Sleepmentioning
confidence: 99%
“…Based on the trait theory, 17 traits differ across people, affect behavior, and importantly, are stable patterns (in behavior, cognitions, and emotions) of habit over time. Though current evidence indicates sleep reactivity indeed differs across individuals (i.e., with varying levels of vulnerability in experiencing situational insomnia), 6,11 negatively affects sleep under stressful conditions (e.g., longer sleep onset latency, nocturnal arousals), 9,12,18 and is associated with maladaptive behaviors (e.g., sleep-interfering behaviors), 19 cognitions (e.g., rumination, dysfunctional sleep beliefs), and emotions (e.g., emotion-oriented coping), 1,20,21 evidence of its temporal stability is lacking (i.e., whether the FIRST is reliably stable over time? ).…”
Section: Introductionmentioning
confidence: 79%